Paradoxical TBC with Tuberculomas and Tubercular Meningoencephalitis in a Pregnant Woman with (SARS-CoV-2) - Musa, Juna; Rahman, Masum; Siddik, Abu Bakar; Ikram, Samar; Ahmetgjekaj, Ilir; Vokshi, Valon; Guy, Ali; Cobo, Anisa; Shoushtarizadeh, Alireza; Abdullahu, Blina; et al. (Archives of Clinical and Medical Case Reports, 2021)
A paradoxical response is a clinical or radiological deterioration of existing or new lesions in tuberculosis patients following treatment. Female gender, HIV infection, length of illness are all known potential risk factors. However, the likelihood of developing a paradoxical response with a concurrent infection of COVID-19 is scarcely reported in the literature, as the circumstance with our patient. In this report, we discuss the case of a 21-year-old woman, at 39 weeks gestation, who presented to the OPD with complaints of headache, coughing, nausea, and abdominal pain. RT-PCR was positive for COVID-19, and radiological imaging was consistent with the diagnosis of Miliary Tuberculosis, further complicated by tuberculous meningitis. Our study aims to highlight the paradox of TB progression in an obstetric patient with prior history of treated TB, coupled with the risk factors associated with a paradoxical reaction.